DETERMINAN KEJADIAN STUNTING: TINJAUAN PEMBERIAN ASI EKSKLUSIF DAN MP-ASI - Lestaluhu, Santi Aprilian; Wakano, Abuzar; Rofiqoh, Rofiqoh (Ensiklopedia of Journal, 2025)
Abstract: Children who experience stunting will have a height that is not appropriate for their age. This problem can have long-term effects on the physical and cognitive development of children, which affects their quality of life in the future. The general objective of this study is to determine the determinants of stunting: a review of exclusive breastfeeding and complementary feeding. The research design used in this study is case control. The study was conducted in the Mangulewa Health Center Working Area, Golewa Barat Subdistrict, Ngada District. The study was conducted in January 2024. The population in this study consisted of all toddlers in Golewa Barat Subdistrict, totaling 654 toddlers, with 136 stunted toddlers and 518 non-stunted toddlers. The sample size was 104, consisting of 52 case samples and 52 control samples. The sampling technique used was probability sampling with the Simple Random Sampling method. The research instrument used was a research questionnaire. Data analysis was conducted using univariate and bivariate methods. The results of the study indicate a relationship between the history of exclusive breastfeeding (p-value: 0.025) and MP ASI (p-value: 0.044) with stunting. It is recommended that mothers of toddlers increase their children's intake of animal protein by modifying animal protein foods into forms and flavors that children prefer, so that children are more interested and do not get bored with the side dishes provided. Since the introduction of complementary foods at 6 months of age, it is important to introduce a variety of animal protein sources to toddlers.Keywords: Exclusive breastfeeding, toddlers, stunting.